Design of a planar filtering power divider with wide-stopband suppression. Issue 8 (17th November 2022) - Hao, Honggang; Xu, Huan; Ling, Qinxuan; Wang, Yunrui
ABSTRACT: According to the development demand for radio frequency module function integration, a filtering power divider with wideband external suppression and high isolation is designed based on the traditional Wilkinson power divider. The working mechanism of the device is analyzed by using the odd-even mode method. Utilizing the branch loading on the coupled-line and the addition of a step impedance open-circuit stub, we can realize the filtering function, widen the passband bandwidth, and improve the performance of stopband rejection. Through the bending of microstrip line between the input and output parts, it is conducive to the physical access of isolation resistance, and the isolation performance between output ports is improved. The research results show that the central working frequency of the filtering power divider is 2.85 GHz ( f 0 ). The 3 dB bandwidth width is 1.51 GHz, and the relative bandwidth is 52.9%. The out-of-band suppression is lower than −20 dB in the range of 3.96 to 11.1 GHz (3.89 f 0 ), and the isolation between output ports is lower than −24.4 dB in the ultra-wideband range of DC to 12 GHz. The device has excellent application prospects in radio frequency communication systems, such as amplifiers and antenna arrays.